Pengaruh Iklan Youtube Terhadap Minat Beli Mahasiswa Polban - Lulu Hasna Luthfiani (International Journal Administration, Business & Organization, 2023)
In this era of globalization, promoting product sales by using advertisements on social media is mostly done by business people. Based on this, the purpose of this study was to determine the effect of advertising from one of the social media, namely Youtube, on the purchase intention of Polban students. This study uses a quantitative approach and a descriptive survey. The data collection technique used by researchers here consists of two types of data, namely primary data taken from respondents' answers to the questionnaire and secondary data taken from literature studies. The analytical method used is to use research statistics in the form of a simple regression analysis regarding the influence of YouTube Advertisements (X) on the Purchase Intention (Y) of Polban students. The result of this analysis is that Youtube Advertisement (X) have an influence on Purchase Intention (Y) in amount of 54.8%. Keywords: Advertising, Youtube, Purchase Intention